Respostas
respondido por:
2
Olá Lohanna,
![x^2(x^2-6)=3(x^4-2x^2).\\
x^4-6x^2=3x^4-6x^2\\
x^4-3x^4-6x^2+6x^2=0\\
-2x^4=0\\
(-2x^2)^2=0\\\\
x^2=k\\\\
-2k^2=0\\\\
k^2= \dfrac{~~0}{-2}\\\\
k^2=0\\
k=\pm \sqrt{0}\\\\
k=\pm0\\\\
k'=k''=k'''=k''''=0\\\\
\large\boxed{S=\{0,0,0,0\}} x^2(x^2-6)=3(x^4-2x^2).\\
x^4-6x^2=3x^4-6x^2\\
x^4-3x^4-6x^2+6x^2=0\\
-2x^4=0\\
(-2x^2)^2=0\\\\
x^2=k\\\\
-2k^2=0\\\\
k^2= \dfrac{~~0}{-2}\\\\
k^2=0\\
k=\pm \sqrt{0}\\\\
k=\pm0\\\\
k'=k''=k'''=k''''=0\\\\
\large\boxed{S=\{0,0,0,0\}}](https://tex.z-dn.net/?f=x%5E2%28x%5E2-6%29%3D3%28x%5E4-2x%5E2%29.%5C%5C%0Ax%5E4-6x%5E2%3D3x%5E4-6x%5E2%5C%5C%0Ax%5E4-3x%5E4-6x%5E2%2B6x%5E2%3D0%5C%5C%0A-2x%5E4%3D0%5C%5C%0A%28-2x%5E2%29%5E2%3D0%5C%5C%5C%5C%0Ax%5E2%3Dk%5C%5C%5C%5C%0A-2k%5E2%3D0%5C%5C%5C%5C%0Ak%5E2%3D+%5Cdfrac%7B%7E%7E0%7D%7B-2%7D%5C%5C%5C%5C%0Ak%5E2%3D0%5C%5C%0Ak%3D%5Cpm+%5Csqrt%7B0%7D%5C%5C%5C%5C%0Ak%3D%5Cpm0%5C%5C%5C%5C%0Ak%27%3Dk%27%27%3Dk%27%27%27%3Dk%27%27%27%27%3D0%5C%5C%5C%5C%0A%5Clarge%5Cboxed%7BS%3D%5C%7B0%2C0%2C0%2C0%5C%7D%7D++)
Tenha ótimos estudos =))
Tenha ótimos estudos =))
Perguntas similares
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás